Enantioselective Synthesis of Atropisomeric Biaryl Phosphorus Compounds by Chiral‐Phosphonium‐Salt‐Enabled Cascade Arene Formation. (1st June 2022) - Zhu, Lixiang; Peng, Heling; Guo, Yan; Che, Jixing; Wu, Jia‐Hong; Su, Zhishan; Wang, Tianli
Abstract: Axially chiral biaryl monophosphorus molecules, exemplified by atropisomeric 1, 1′‐biaryl aminophosphines, are significant motifs in numerous chiral ligands/catalysts. Developing efficient methods for preparing phosphorus compounds with these privileged motifs is an important endeavor in synthetic chemistry. Herein, we develop an effective, modular method by a chiral‐phosphonium‐salt‐catalyzed novel cascade between phosphorus‐containing nitroolefins and α, α‐dicyanoolefins, leading to a great diversity of atropisomeric biaryls bearing phosphorus groups in high yields with excellent stereoselectivities. The reaction features include a Thorpe‐type cycloaddition/oxidative hydroxylation/aromatization cascade pathway with a central‐to‐axial chirality transfer process. Insight gained from our studies is expected to advance general efforts towards the catalytic synthesis of atropisomeric biaryl phosphorus compounds, offering a platform for developing new efficient chiral ligands and catalysts. Abstract : A highly enantioselective organocatalytic cascade process has been developed for the synthesis of axially chiral 1, 1′‐biaryl phosphorus compounds. The approach involves multistep arene formation promoted by multifunctional phosphonium salt catalysis and proceeds through a complex Thorpe‐type cycloaddition/oxidative hydroxylation/aromatization cascade with central‐to‐axial chirality transfer.